Examining heterogeneity in depression symptoms and associations with cognition and everyday function in MCI. Issue 3 (16th March 2022) - Divers, Ross; Robinson, Anthony; Miller, Luke; Davis, Katrail; Reed, Christopher; Calamia, Matthew
ABSTRACT: Introduction: Although there is some evidence that different symptoms of depression have differential effects on cognition in older adults, these relationships remain understudied in older adults with mild cognitive impairment (MCI). Method: Older adults (>50 years old) were classified as having MCI by Alzheimer's Disease Research Centers (ADRCs). Exploratory factor analyses and factor mixture modeling were used to determine depression symptom classes. Classes were then compared across different domains of cognition (i.e., memory, attention, language, and executive function) and informant-rated everyday function. Results: Analyses revealed six, distinct symptom classes (i.e., somatic symptoms, severely depressed, anhedonic symptoms, cognitive symptoms, minimally depressed, and low life satisfaction symptoms). Classes significantly varied on all measures of cognition and everyday function. In particular, the anhedonic class often showed the most substantial decline (on par with the severely depressed class), while the low life satisfaction class often showed the least (on par with the minimally depressed class). Conclusions: To our knowledge, this is the first study to examine the relationship between depression symptom profiles and cognitive and everyday function in those with MCI. Our findings show that depression symptoms greatly differ in their associations with cognitive and everyday function. It may be beneficial for clinicians to specifically note if patients with MCI are reporting anhedonic and somatic symptoms of depression specifically.